EKSPLORASI ETNOMATEMATIKA RUMAH PANGGUNG BETAWI SI PITUNG DALAM PANDANGAN AKTIVITAS FUNDAMENTAL MATEMATIS BISHOP - Gerry Filiestianto; Sheilla Zalzabilla Al-Jabar (IKIP Siliwangi, 2022)
Mathematics is an applied science found in every activity of human daily life, including in the field of culture. According to Alan Bishop regarding the fundamental mathematical activity found in every human life. In education, mathematics is often considered a subject that makes it difficult for educators to teach as well as for students to implement it in everyday life. Therefore, students can be provided with understandings of mathematical activities that can be found in the surrounding environment, especially with cultural products that can indirectly make students participate in preserving culture. In the latest science there is a term that connects mathematical science with culture called ethnomathematics. In Betawi culture, there are objects related to the term ethnomathematics including the Betawi Si Pitung Stage House which is a relic of the assimilation of other ethnic cultures. The purpose of this study is to determine the fundamental mathematical activities according to Bishop contained in the Betawi Si Pitung Stage House. This research uses qualitative research methods with an ethnographic approach and data collection techniques in the form of observation, interviews and literature review. From the research conducted, it is known that there are activities related to fundamental mathematical aspects such as numbering activities, locating, measuring, designing, playing, and explaining activities at the Betawi Si Pitung Stage House.